Neural Network Underlying Recovery from Disowned Bodily States Induced by the Rubber Hand Illusion - In-Seon Lee; Younbyoung Chae (Neural Plasticity)
We used functional magnetic resonance imaging to investigate how causal influences between brain regions during the rubber hand illusion (RHI) are modulated by tactile and visual stimuli. We applied needle rotations during the RHI in two different ways: one was with the real hand (reinstantiation by tactile stimuli, R-TS) and the other was with the rubber hand (reinstantiation by visual stimuli, R-VS). We used dynamic causal modeling to investigate interactions among four relevant brain regions: the ventral premotor cortex (PMv), the intraparietal sulcus (IPS), the secondary somatosensory cortex (SII), and the lateral occipitotemporal cortex (LOC). The tactile aspects of needle rotations changed the effective connectivity by directly influencing activity in the SII, whereas visual aspects of needle rotation changed the effective connectivity by influencing both the SII and the LOC. The endogenous connectivity parameters between the IPS and the PMv were reduced significantly in the R-TS condition. The modulatory parameters between the IPS and the PMv were enhanced significantly in the R-TS condition. The connectivity patterns driven by disowned bodily states could be differentially modulated by tactile and visual afferent inputs. Effective connectivity between the parietal and frontal multimodal areas may play important roles in the reinstantiation of body ownership.